Impact of hypofractionated schemes in radiotherapy for locally advanced head and neck cancer patients. (7th May 2019) - Franzese, Ciro; Fogliata, Antonella; Franceschini, Davide; Navarria, Pierina; Cozzi, Luca; Tomatis, Stefano; De Virgilio, Armando; Spriano, Giuseppe; Scorsetti, Marta
Abstract : Objective: To analyze two cohorts of locally advanced head and neck cancer (LAHNC) patients treated with two schedules of hypofractionated radiotherapy and 5 versus 3 mm clinical target volume–planning target volume (CTV‐PTV) margins. Methods: 145 patients were included. The patient cohort was divided into two groups. Group A included 97 patients treated with 69.96/54.45 grays (Gy) to the high‐risk and low‐risk volumes, respectively, in 33 fractions, with 5 mm margins. Group B included 48 patients treated with 66/54 Gy in 30 fractions using 3 mm margins. Toxicity was recorded according to the Common Toxicity Criteria version 3. Patient outcomes for locoregional control (LRC), disease‐free survival (DFS), and overall survival (OS) were determined. Results: Median follow‐up was 26 months. In terms of toxicity, acute dysphagia worsened significantly ( P = 0.003) in group B, whereas acute salivary toxicity tended to significance ( P = 0.071). No significant late toxicity differences were recorded. Rates of LRC at 1 and 2 years were 90.1% ± 2.6% and 84.2% ± 3.4%, respectively, with superiority for group A ( P = 0.045). The statistical significance remained for the low‐dose level ( P = 0.007) but not for high dose ( P = 0.110). Rates of DFS at 1 and 2 years were 84.9% ± 3.1% and 76.5% ± 3.9%, respectively, whereas rates of OS were 95.9% ± 1.8% and 91.6% ± 2.7%, respectively. No differences were observed between the two groups in terms of DFS ( P = 0.270) and OS ( P = 0.152). Conclusion: The use of reduced CTV to PTV margins and dose reduction with hypofractionation schedule can improve the pattern of toxicity in LAHNC patients. This approach resulted in an increased rate of locoregional progression, particularly in low‐risk regions. Level of Evidence: 4 Laryngoscope, 130:E163–E170, 2020